Perspektif Maqashid Al-Syariah terhadap Ta'zir dan Ta'widh dalam Mitigasi Moral Hazard Nasabah Bank Syariah di Indonesia - Safwira Guna Putra; Muslihun (Jurnal Perbankan Syariah, 2026)
Islamic banking prioritizes wealth protection (li hifz al-mal) as a core principle in financing contracts, yet faces significant moral hazard risks from customers who delay or default on payment obligations. This study examines the implementation of ta'zir and ta'widh in Indonesian Islamic banking as instruments for mitigating moral hazard within the maqashid syariah framework. Employing a qualitative approach with a normative empirical design, data were collected through in-depth interviews with informants selected purposively based on their relevance and expertise, and analyzed using the interactive model by Miles and Huberman. The findings reveal that ta'zir and ta'widh are understood as multidimensional instruments: protecting the wealth of depositors, disciplining and educating borrowers, and enforcing contractual justice. Ta'zir functions as a preventive and educational sanction, while ta'widh serves as compensation for actual losses incurred due to default. Islamic banks clearly distinguish between customers who intentionally delay payment and those who are genuinely unable to pay. In cases of genuine inability, banks refrain from demanding margins and fines, yet ensure principal repayment to safeguard the rights of depositors. This study strengthens the argument that maqashid syariah operates not only at the normative level but is effectively translated into institutional instruments and operational practices in Islamic banking. The practical implications call for Islamic banks to strengthen education and socialization regarding the normative objectives of ta'zir and ta'widh, ensuring transparent, consistent, and socially beneficial application. Keywords: ta'zir, ta'widh, maqashid syariah, moral hazard, Islamic banking.